(untitled) (مجلة ديالى للبحوث الانسانية, 2022)
Thise paper includes the synthesis and characterization of the complexes of the amino acid (L-proline) = C5H9NO2) symbolized (proH)-with some metal . The ligand and metal ions were brought into reaction in ethanolic medium using (1:2) metal : ligand molar ratios as required. Products were found to be solid crystalline complexes, which have been Characterized through the following techniques : Melting points, Solubility, Molar conductivity